Investigación e Innovación Responsable: un nuevo enfoque de la Comisión Europea para regular el desarrollo tecnológico (Tecnología y Sociedad, 2018)
This article focuses on developing the concept of Responsible Research and Innovation (RRI), a conceptual framework proposed to progress in the ways of channeling research and innovation processes and their insertion in societies. The article elaborates on the context in which the concept arises and an analysis is made on the different definitions currently present in related literature, although there is still no one fully agreed description and ideas about how it should be implemented vary. Finally, the significant aspects are mentioned and critical positions thathave emerged in relation to this proposal in recent years are discussed.
Keywords: Responsible Research and Innovation; Technological development; Technological evaluation; Science; Technology and society